Preparation of losartan loaded starch nanoparticles by high-speed shear-inverse miniemulsion method - DUAN Chao; ZHANG Kun-ming; HUANG Yong-chun; ZHENG Jian-bin; TANG Xiang-yi (Shipin yu jixie)
Objective: This study aimed to explore the feasibility of preparation of loaded losartan starch nanoparticles by high-speed shear-reverse microemulsion crosslinking. Methods: Using losartan as model drug and sodium trimetaphosphate as crosslinking agent, the effects of starch solution concentration, sodium trimetaphosphate addition amount, crosslinking time and shear rate on particle size and yield of starch nanoparticles were investigated. Optical micrography, infrared spectrometer and X-ray diffraction were used to characterize losartan loaded starch nanoparticles. Results: The optimal preparation process of nanoparticles was 15% starch solution concentration, 25% sodium trimetaphosphate, 3 h crosslinking time, 5 000 r/min shear rate. Under the control of these conditions, the minimum size of nanoparticles was 755.2 nm, and the yield reached 69.5%. Optical micrography showed that the nanoparticles were round, full and spherical. FTIR showed that losartan was successfully loaded into starch nanoparticles. XRD showed that the nanoparticles exist in amorphous structure. Conclusion: Small particle size drug-carrying starch nanoparticles can be prepared by high-speed shear coupled reversed-phase fine emulsion crosslinking method.